Self transcendence concept analysis. Importance in nursing care for the elderly - Raúl Fernando Guerrero Castañeda; Ma. Guadalupe Ojeda Vargas (Universidad de Alicante, 2015)
Introduction: The Self-Transcendence is a connection with the being, an advance in optimizing of the human realization, on deeper contexts: the spiritual. Objective: Analyze the concept of "self-transcendence" and propose their use in nursing care for the elderly. Material and methods: It was analyzed the concept of "Self-transcendence" (method from Walker & Avant). Identification of conceptual elements, review of literature and conceptual proposal; Descriptors: "Self-transcendence" "Nursing" (Spanish, English, Portuguese). Results: Conceptual elements: Capacity of human being, Go beyond self, Expand personal bounds, Spiritual path, Giving meaning to life, connection with self, others, the environment, connection with the spirit of the universe, Find meanings of own existence. Conceptual proposal: "It is the ability of the human being to go beyond the self and consequently expand the personal bounds by a spiritual path to give meaning to life and that links to a connection with self, others, the environment and the spirit of the universe; as a meaning of existence itself". Conclusions: Self-Transcendence is a complex phenomenon that varies from specific situations, like entering in process of improvement and personal aspirations; and complex as mourning or death.